Application of the Servqual Method in Studies on the Quality of Services Provided by the Agricultural Social Insurance Fund - Witkowska, Justyna (Olsztyn Economic Journal, 2012)
This paper presents the application of the Servqual method in studies on the quality of services provided among the clients of the Agricultural Social Insurance Fund (KRUS). The clients evaluated five dimensions of the service provided in three aspects: the expected quality, the actual quality and the minimum quality. Thanks to the studies conducted, identification of gaps that emerged in the service provision process was possible. The respondents rated the quality of service provided by the KRUS as representing a relatively high level.